Preparation of magnetic nanoparticles via chemically induced transition: Dependence of components and magnetization on the concentration of treating solution used. (11th January 2017) - Chen, Yanshuang; Chen, Qin; Mao, Hong; Zhang, Ting; Qiu, Xiaoyan; Lin, Yueqiang; Li, Jian
Using an FeOOH/Mg(OH)2 precursor, maghemite-based magnetic nanoparticles can be prepared by a chemically induced transition in an Iron(II) chloride (FeCl2 ) treating solution. FeCl2 solutions of various concentrations were used to investigate the dependence of sample components and magnetization on the treating solution. The bulk chemical species, crystal structures, surface chemical components, morphologies, and specific magnetizations of the samples were characterized. When the concentration of FeCl2 solution was in a moderate range of 0.060–0.250 M, maghemite nanoparticles coated by hydromolysite, that is, maghemite/hydromolysite nanoparticles, could be prepared. At lower concentrations, below 0.030 M, the samples contained maghemite/hydromolysite and magnesium oxide nanoparticles, and at higher concentrations, up to 1.000 M, the samples contained maghemite/hydromolysite and hydromolysite nanoparticles. The molar and mass percentages of each phase were estimated for each sample. The apparent magnetization behavior of the samples, which exhibited a non-monotonic variation with increasing concentration of FeCl2 solution, is explained from the variation of mass percentage of the maghemite phase with concentration.